A feed-based typology of crop-livestock systems in Eastern Africa - Paul, Birthe K.; Peters, Michael; Groot, Jeroen C.J.; Herrero, Mario; Tittonell, Pablo A. (International Center for Tropical Agriculture, 2013)
Poster presented at Tropentag 2013, September 17 - 19, 2013, Stuttgart-Hohenheim